Relationship between red blood cell membrane fatty acid composition and dietary fatty acids level in obese adolescents with/without metabolic syndrome - Güneş, Ömer; Soylu, Meltem; İnanç, Neriman; Tascılar, Emre; Sertoğlu, Erdim; Taş, Ahmet; Serdar, Muhittin A.; Özcan, Okan (Progress in Nutrition, 2018)
Background: Dietary lipids may lead to significant changes in the composition of cell membrane structure. Objective: The association between red blood cell (RBC) membrane fatty acid composition and dietary fatty acids intake in obese adolescents with and without metabolic syndrome was investigated. Methods: Ninety-six adolescents (59 obese and 37 lean) were included in the study. The obese subjects were divided into two groups with (n=26, aged 12.3 years ) and without (n=33, aged 12.7 years) metabolic syndrome. The mean age of lean participants was 11.8. The criteria for metabolic syndrome were: 10